Tindak Tutur Penolakan Dalam Keluarga Pada Drama Kyou Mo Iyagarase Bentou : Kajian Pragmatik - Amalia, Aan (Vocational College of Diponegoro University, 2024)
This study aims to find out about the speech acts of refusal that are generally used in Japanese families. The research method used is a descriptive method with pragmatic equivalent data analysis.The object of research is the drama Kyou Mo Iyagarase Bentou. In the drama Kyou Mo Iyagarase Bentou, it was found that speech acts of rejection in Japanese families almost do not use the concept of aimai to protect the feelings of the interlocutor, while speech acts of rejection in Japanese society in general are delivered politely and carefully and even seem ambiguous. Japanese people usually do not want to offend their conversation partner, in accordance with Japanese culture with the concept of aimai, but statements of rejection within the family are conveyed as they are.From the research results, seven (7) indirect rejection speech acts were found in dialogues 1, 2, 3, 4, 5 and 7, two (2) direct rejection speech acts in dialogues 1 and 6. This indicates that even though when refusing you do not think about the feelings of the conversation partner, you still consider the feelings of the conversation partner by not directly stating the refusal that is being conveyed. Keyword : speech act, refusal, drama, direct, indirect